Effect of crossbreeding and sex on slaughter performance and meat quality in Xingguo gray goose based on multiomics data analysis - Jiangnan Huang; Linjie Rao; Weihong Zhang; Xiaolian Chen; Haiqin Li; Fanfan Zhang; Jinfang Xie; Qipeng Wei (Poultry Science, 2023)
ABSTRACT: Here, we examined the effects of crossbreeding and sex on growth performance, slaughter performance, and meat quality in Xingguo gray (XG) goose, using transcriptomic and metabolomic techniques. The experiment was conducted using 400 goslings (1-day old) of 2 genotypes: the XG breed and its ternary hybrids [F2 geese; (XG Goose♂ × Yangzhou Goose♀)♀ × Shitou Goose♂]. The goslings were divided into 4 groups: female XG, male XG, female F2 geese, and male F2 geese, and growth parameters were examined at 70 d of age, using 30 birds from each group. Following slaughter, samples of breast and thigh muscles were collected from each group for chemical, metabolome, and transcriptome analyses. Growth rate, live body and slaughter weights, meat chemical composition, and muscle fiber diameter were affected by crossbreeding and sex. Crossbreeding significantly improved the dressing percentage, semieviscerated rate, eviscerated yield, and abdominal fat yield of XG geese. To clarify the potential regulatory network affected by crossbreeding and sex, we used RNA-seq and nontargeted metabolomics to detect changes in male and female goose breast muscle. The transcriptome results showed that there were 534, 323, 297, and 492 differently expressed genes (DEGs) among the 4 comparison groups (XG-Female vs. F2-Female, XG-Male vs. F2-Male, F2-Male vs. F2-Female, and XG-Male vs. XG-Female, respectively) that were mainly related to muscle growth and development and fatty acid metabolism pathways. A total of 141 significantly differentially accumulated metabolites (DAMs) were enriched in serine and threonine, propionate, and pyruvate metabolism. Finally, we comprehensively analyzed the metabolome and transcriptome data and found that many DEGs and DAMs played crucial roles in lipid metabolism and muscle growth and development. In summary, crossbreeding can improve XG goose production performance and affect breast muscle gene expression and metabolites in both female and male geese.